Performing Everyday Life in Argentine Popular Theater, 1890-1934 - Garrett, Victoria Lynn (New Directions in Latino American Cultures, 2018)
This book examines the prolific and widely-attended popular theater boom of the género chico criollo in the context of Argentina's modernization. Victoria Lynn Garrett examines how selected plays mediated the impact of economic liberalism, technological changes, new competing and contradictory gender roles, intense labor union activity, and the foreign/nativist dichotomy. Popular theaters served as spaces for cultural agency by portraying conventional and innovative performances of daily life. This dramatic corpus was a critical mass cultural medium that allowed audiences to evaluate the dominant fictions of liberal modernity, to critique Argentina's purportedly democratic culture, and to imagine alternative performances of everyday life in accordance with their realities. Through a fresh look at the relationship among politics, economics, popular culture, and performance in Argentina's modernization period, the book uncovers largely overlooked articulations of popular-class identities and desires for greater inclusion that would drive social and political struggles to this day.